Photodegradation of acetaminophen and sulfamethoxazole by visible-light-responsive g-C3N4 based 2D photocatalysts - Paragas, Larah Kriselle B.
Emerging contaminants like pharmaceutical products, particularly antibiotics and paracetamol pose threats to human and environment due to the significantly large concentration being released in the waterways. Recent studies have not yet found a cost effective and efficient way of purification. In this study, a facile synthesis method of co pyrolysis of urea, potassium iodate and cerium nitrate produced an outstanding visible light photocatalyst for the efficient removal of Acetaminophen (ACT) and Sulfamethoxazole (SMX). The composite catalyst with mass content of 15% CeO2 demonstrated the optimum condition by degrading ACT by 22 and 35.4 times as high as pure g-C3N4 and CeO2, respectively. Meanwhile, the best condition for the decomposition of SMX was observed in 50% iodine and potassium doping of g-C3N4 with more than 99% removal in 40 mins. Influences of various parameters (catalyst dosage, initial pollutant concentration, dopant content, pH) and the photodegradation behavior with anions interference (NO3-, SO42-, C1-, PO43-) were also discussed. Active species trapping experiment confirmed that O2- and h played the significant role in the improved photocatalytic degradation which elucidate that the as-synthesized nanocomposites established a Z-scheme system. The highly enhanced performance of CeO2/IK-C3N4 under visible light is attributed to the synergistic effect of the exchanges between iodine, CeO2 and carbon nitride nanosheets ensuing lasting separation of photo-induced charge carriers and amplification of visible light response. Moreover, the abundance of these elements in the environment may produce a low cost material which can be fabricated at a large scale to potentially aid the society in resolving crisis in environmental detoxification.